محدثین و فقہاء کے اصولِ استنباط و استدلال: ایک تطبیقی مطالعہ: Principles of Derivation and Reasoning of the Hadith Scholars and Jurists: A Comparative Study - Hafiz Asif Ismail; Dr. Muhammad Asim Shahbaz (jihat-ul-islam, 2024)
This study explores the principles of istinbāṭ (derivation) and istidlāl (reasoning) employed by the scholars of Hadith (muhaddithīn) and Islamic jurists (fuqahā’). It aims to highlight the methodological foundations through which both groups derived religious rulings and interpreted textual evidence from the Qur’an and Sunnah. The research conducts a comparative analysis of their approaches, examining points of convergence and divergence in their interpretative frameworks. The muhaddithīn emphasized authenticity, context, and textual precision in deriving rulings, while the fuqahā’ focused on comprehensive legal reasoning, analogical deduction, and the objectives of Shariah (maqāṣid al-sharī‘ah). Through this analytical and comparative lens, the study demonstrates how both disciplines collectively contributed to the preservation, understanding, and application of Islamic law. It further emphasizes the importance of harmonizing their methodologies to enhance contemporary Islamic jurisprudence and scholarly discourse.